Intravenous Thrombolysis by Telestroke in the 3- to 4.5-h Time Window - Simon, Erik; Forghani, Matin; Abramyuk, Andrij; Winzer, Simon; Wojciechowski, Claudia; Pallesen, Lars-Peder; Siepmann, Timo; Reichmann, Heinz; Puetz, Volker; Barlinn, Kristian; Barlinn, Jessica (Frontiers in Neurology, 2021)
Background: While intravenous thrombolysis (IVT) in ischemic stroke can be safely applied in telestroke networks within 3-hours from symptom onset, there is lack of evidence for safety in the expanded 3- to 4.5-hour time window. We assessed safety and short-term efficacy of IVT in acute ischemic stroke (AIS) in the expanded time window delivered through a hub-and-spoke telestroke network. Methods: Observational study of acute ischemic stroke (AIS) patients who received IVT at the Stroke Eastern Saxony Telemedical Network between 01/2014 and 12/2015. We compared safety data including symptomatic intracerebral hemorrhage (sICH; according to ECASS II definition) and any ICH between patients admitted to telestroke spoke sites and patients directly admitted to a tertiary stroke center representing the hub of the network. We also assessed short-term efficacy data including favorable functional outcome (i.e., mRS ≤ 2) and NIHSS at discharge, hospital discharge disposition as well as in-hospital mortality. Results: In total, 152 AIS patients were treated with IVT in the expanded time window (spoke sites, n=104 [26.9%]; hub site, n=48 [25.9%]). Patients treated at spoke sites had less frequently a large vessel occlusion (8/104 [7.7%] versus 20/48 [41.7%]; p<0.0001), a determined stroke etiology (p<0.0001) and had slightly shorter onset-to-treatment times (210 [45] versus 228 [58] minutes; p=0.02) than patients who presented to the hub site. Both cohorts did not display any further differences in demographics, vascular risk factors, median baseline NIHSS scores or median baseline ASPECTS (p>0.05). There was no difference in the frequency of sICH (4.9% vs 6.3%; p=0.71) or any ICH (8.7% vs. 16.7%; p=0.15). Neither there was a difference regarding favorable functional outcome (44.1% vs. 39.6%; p=0.6) or median NIHSS (3 [5.5] versus 2.5 [5.75); p=0.92) at discharge, hospital discharge disposition (p=0.28) or in-hospital mortality (9.6%; vs. 8.3%; p=1.0). Multivariable modeling did not reveal an association between telestroke and sICH or favorable functional outcome (p>0.05). Conclusions: Delivery of IVT in the expanded 3- to 4.5-hour time window through a telestroke network appears to be safe with equivalent short-term functional outcomes for spoke and hub center admissions.